2018
DOI: 10.1021/acsphotonics.8b01280
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Height Tuning of Terahertz Quantum Cascade Lasers for High-Temperature Operation

Abstract: Terahertz quantum cascade lasers (QCLs) are excellent coherent light sources, but are still limited to an operating temperature below 200 K. To tackle this, we analyze the influence of the barrier height for the identical three-well terahertz QCL layer sequence by comparing different aluminum concentrations (x = 0.12–0.24) in the GaAs/AlxGa1-xAs material system, and then we present an optimized structure based on these findings. Electron injection and extraction mechanisms as well as LO-phonon depopulation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…We provide detailed discussion on different THz QCL designs and investigate the paradigm shift introduced in the latest record performance [14] in terms of increasing the energy separation between states designed to assist the lasing process through LO-phonon scattering. This has also been noticed in earlier experimental works which focussed on barrier height optimisation [40] and temperature performance optimisation [41].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…We provide detailed discussion on different THz QCL designs and investigate the paradigm shift introduced in the latest record performance [14] in terms of increasing the energy separation between states designed to assist the lasing process through LO-phonon scattering. This has also been noticed in earlier experimental works which focussed on barrier height optimisation [40] and temperature performance optimisation [41].…”
Section: Introductionsupporting
confidence: 74%
“…There were several experimental works that have discussed whether the optimal value of LO-phonon transition should be higher. Work in [40] has explored the effect of barrier height on a particular design which inadvertently increased the transition above 36 meV and work in [41] directly investigated whether optimal design value should be focussed at 40 meV for a particular three well structure. The most recent temperature record of 250 K [14] is the first experimental demonstration that employed 51 meV LO-phonon transition and thus addressed the LO-phonon leakage issues at high temperature and it is worth considering whether temperature performance of other designs can be improved further to suppress leakage of ULL towards other levels.…”
Section: Design Improvement With Lo-phonon Transitions At Higher Energymentioning
confidence: 99%
“…For instance, the degraded PI is also reported to originate primarily from thermal backfilling and slow extraction of electrons at the lower state rather than the increasing phonon emission rate at the upper state. [ 3,23–25 ] In another case, the parasitic leakage channel is speculated to have little impact on PI at high temperature since a small fraction of electrons reside at continuum levels according to calculations, [ 13 ] yielding inconsistent with other studies. [ 3,5 ] In addition, discrepancies often emerge between theoretical computations and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz quantum cascade laser (THz QCL), as a compact optical source for terahertz frequency range (1.2–5.4 THz), [ 1 ] has undergone tremendous development since its first demonstration in 2001. [ 2–6 ] Nonetheless, the cryogenic cooling must be exploited during the THz QCL operation due to its rapid performance degradation at elevated temperature, [ 7 ] which has impeded its practical application in many areas, such as security, astrophysics, and medical treatment. To this date, while the most progressive THz QCL based on phonon‐tunneling design could be operated at the maximum temperature of 250 K in pulse mode, [ 5 ] there exists a certain distance from room‐temperature operation, and its luminous efficiency deteriorates rapidly at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that THz QCL quantum structure designs are critical for the temperature performance of the devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and have made great efforts to explore different THz QCL quantum structure designs. Multiple quantum designs, such as the bound-to-continuum (BTC) design [6,11,17,18], resonantphonon (RP) design [19][20][21], scattering-assisted (SA) design [4,22], phonon-photon-phonon (3p) design [23][24][25], direct-phonon design [26,27], split-well direct-phonon design [28,29], extraction-controlled design [30,31], and hybrid extraction/injection design [32], have been experimentally demonstrated and exhibited good temperature performance at different frequencies of ~1. 3-5.4 THz [33].…”
Section: Introductionmentioning
confidence: 99%